Global environmental initiatives of the EU in Antarctica: Ukraine’s position harmonization and prospect (preceding Ukraine’s chairmanship in the CCAMLR, 2023–2024) - A. Fedchuk; S. Zherebchuk; D. Cheberkus (Ukrainian Antarctic Journal, 2021)
With the strengthening of the global environmental movement, the Southern Ocean has become an effective international testing ground for the development of spatial planning in marine environments beyond national jurisdiction. This note aims to review the European Union (EU) role in the progress on designation of environmentally representative network of marine protected areas (MPAs) in Antarctica, and the effect of this process on the shaping of Ukraine’s strategy in this region. Following Ukraine’s external vector to European integration, in 2021 the country began formally aligning as a co-proponent with the EU-initiated two MPA proposals — in East Antarctica and the Weddell Sea. This alignment of positions is utterly important, taking into account the approaching of Ukraine's first chairmanship of the Commission for the Conservation of Antarctic Marine Living Resources in 2023–2024, which would be an exceptional opportunity for our country to make a significant progress in designation the largest MPAs ever implemented in Antarctica given national interests, including the creation of an international consortium with the involvement of Ukrainian scientific infrastructure in Antarctica, such as Ukrainian Antarctic Akademik Vernadsky station and the research vessel Noosfera, to implement internationally significant scientific and monitoring programs to evaluate MPAs efficiency with Ukraine as a co-initiator.